2018
DOI: 10.1002/adhm.201800889
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Delivery Nanosystems Formed by Degradable Antibacterial Poly(Aspartic Acid) Derivatives for Infected Skin Defect Therapy

Abstract: Nucleic acid (NA)‐based therapy is promising for tissue repair, such as skin and bone defect therapy. However, bacterial infections often occur in the process of tissue healing. The ideal treatment of tissue repair requires both anti‐infection and simultaneous tissue healing. The epidermal growth factor (EGF) plays an important role in wound healing processes. In this work, degradable antibacterial gene vectors based on tobramycin (clinically relevant antibiotic) conjugated poly(aspartic acid) (TPT) are propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Song et al reported a polyplex of a plasmid encoding EGF with PASA, formed by ROP of NCA with the antibiotic tobramycin employed as an initiator and subsequent constituent. 123 Evaluation of this polyplex in a rat in vivo skin wound healing model demonstrated an adequate degradation profile, low cytotoxicity, hemocompatibility, antibacterial activity, and the robust ability to transfect fibroblasts and increase proliferation.…”
Section: Paa-based Vectors For Skin Deliverymentioning
confidence: 97%
“…Song et al reported a polyplex of a plasmid encoding EGF with PASA, formed by ROP of NCA with the antibiotic tobramycin employed as an initiator and subsequent constituent. 123 Evaluation of this polyplex in a rat in vivo skin wound healing model demonstrated an adequate degradation profile, low cytotoxicity, hemocompatibility, antibacterial activity, and the robust ability to transfect fibroblasts and increase proliferation.…”
Section: Paa-based Vectors For Skin Deliverymentioning
confidence: 97%
“…The combined plasmid pKR-p53, which can simultaneously express photosensitive protein (KillerRed) and apoptosis-related protein (P53) in the same cell to achieve the combined therapy of p53-mediated gene/PDT therapy [22] was used to verify the gene delivery ability of The epidermal growth factor (EGF) can effectively promote tissue healing by stimulating the proliferation and migration of keratinocytes, endothelial cells, and fibroblasts. [23] pEGF delivered by an excellent gene vector can overcome the reduction of EGF in wounds, [24] and was chosen to further confirm the gene delivery ability of…”
Section: Biocompatibility and Bioreducibility Of Mpeg 225 -B-pss Nmentioning
confidence: 99%
“…More recently, multifunctional delivery nanosystems containing conjugated tobramycin was developed to eradicate bacterial infections for wound tissue recovery . The tobramycin‐conjugated nanosystems were synthesized by ring‐opening reaction of β‐benzyl‐l‐aspartate N‐carboxy anhydride (BLA‐NCA) starting from the amino groups of tobramycin.…”
Section: Biodegradable Polymeric Nanosystems Containing Antibioticsmentioning
confidence: 99%
“…b) Photographs of wound healing processes of rat model. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Biodegradable Polymeric Nanosystems Containing Antibioticsmentioning
confidence: 99%